Melampaui Hukum Reformasi: Legitimasi Budaya dan Dinamika Politik dalam Mempertahankan Pernikahan Dini Di Kalimantan Tengah - Rizky Ardiansyah, Bagas; Thareq, Subhan Ilham; Annas Puji Yulianto (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
Early marriage in Indonesia, particularly in Central Kalimantan, is a complex social phenomenon with multidimensional impacts on health, education, and the economy. Despite regulations such as Law No. 16 of 2019, which raises the minimum age for marriage, the practice persists due to the interaction between cultural values, policy gaps, and local political dynamics. This study aims to analyze the relationship between marriage dispensation policies, cultural legitimacy, and local political power, as well as explore the role of Generation Z as agents of social change in promoting policy reform. Using John Kingdon’s Multiple Streams Framework (MSF) and Talcott Parsons’ structural functionalism theory, the results show that the three streams in the MSF (problem, policy, and political streams) do not run synchronously and instead reinforce the practice of early marriage. This occurs because culture justifies the practice, policy legalizes it, and politics protects it. In addition, marriage dispensations are often misused as a solution to social, economic, and cultural pressures. These findings highlight the importance of Generation Z’s role as agents of change in advocating for more progressive policies, by promoting reform through education and greater critical awareness of early marriage.